2023
DOI: 10.3390/s23042093
|View full text |Cite
|
Sign up to set email alerts
|

A Federated Learning Multi-Task Scheduling Mechanism Based on Trusted Computing Sandbox

Abstract: At present, some studies have combined federated learning with blockchain, so that participants can conduct federated learning tasks under decentralized conditions, sharing and aggregating model parameters. However, these schemes do not take into account the trusted supervision of federated learning and the case of malicious node attacks. This paper introduces the concept of a trusted computing sandbox to solve this problem. A federated learning multi-task scheduling mechanism based on a trusted computing sand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Liu et al [35] presented a federated learning-based multi-task scheduling mechanism for edge computing that utilizes trusted computing sandbox technology. The proposed mechanism aims to improve the efficiency and security of task scheduling in edge computing environments.…”
Section: ) Federated Learning Based Methods For Task Schedulingmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [35] presented a federated learning-based multi-task scheduling mechanism for edge computing that utilizes trusted computing sandbox technology. The proposed mechanism aims to improve the efficiency and security of task scheduling in edge computing environments.…”
Section: ) Federated Learning Based Methods For Task Schedulingmentioning
confidence: 99%
“…Researchers have identified that the presence of multiple edge devices with diverse computing power, network bandwidth, and varying security levels can be a potential threat to the security of task scheduling. To mitigate these security risks, various security mechanisms have been proposed to ensure the confidentiality, integrity, and availability of data in fog computing systems [35], [69]. However, these proposed solutions need to be tested and evaluated comprehensively to ensure their effectiveness and efficiency.…”
Section: Open Issues and Challengesmentioning
confidence: 99%
“…For the purpose of handling the problem of the unpredictability of tasks and QoS requirements of users in Fog Computing, the authors in [37] have proposed three different DRL-based solutions, with the aim of maximizing rewards with reference to resource utilization, designed as the Markov Decision Process, by taking into consideration the task priority, energy consumption, and latency as the QoS factors. Another effort has been made in [38] for a trusted supervision of federated learning and malicious node attacks by smart contract; they proposed the concept of a decentralized trusted computing sandbox, which is a federated learning multi-task scheduling mechanism using DRL to solve the resource scheduling optimization problem. Both of these two studies have not incorporated Blockchain in their proposed ideas of resolving the scheduling optimization problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To reduce private information exposure during the processing and transmission of components, HFL can employ homomorphic encryption systems [30][31][32], differential privacy mechanisms [33][34][35], and safe aggregation frameworks [36][37][38]. Other methods include blockchain-based FL [39,40] and multi-task FL [41,42].…”
Section: Related Workmentioning
confidence: 99%